Evaluation of the molecular response of corpora lutea to manganese–amino acid complex supplementation in gilts. (17th August 2021) - Studer, Jamie M; Kiefer, Zoe E; Goetz, Brady M; Keating, Aileen F; Baumgard, Lance H; Rambo, Zachary J; Schweer, Wesley P; Wilson, Mark E; Rapp, Christof; Ross, Jason W
Abstract: Porcine pregnancy establishment and maintenance are dependent on the formation of functional corpora lutea (CL ). Manganese (Mn) is critical for CL function as it is a cofactor for Mn superoxide dismutase and enzymes involved in cholesterol synthesis. Previously, we have shown that luteal Mn content increased and luteal progesterone (P 4 ) concentration decreased in the CL of gilts fed diets supplemented with an Mn–amino acid complex (Availa-Mn; Zinpro Corporation) compared with controls fed Mn sulfate. Importantly, serum P4 increased from 0 (estrus onset) to 12 d post estrus (dpe ), as expected, but P4 abundance in circulation was not affected by dietary Mn source ( P = 0.15). We hypothesized that a more bioavailable Mn source (which results in increased luteal Mn content) would alter the luteal proteome and abundance of mRNA associated with steroid biogenesis during the mid-luteal phase of the estrous cycle. Postpubertal gilts ( n = 32) were assigned to one of the four gestation diets. The control diet (CON ) contained 20 ppm of supplemental Mn in the form of Mn sulfate. Three additional diets included 20 (TRT1 ), 40 (TRT2 ), or 60 (TRT3 ) ppm of supplemental Mn in the form of a Mn–amino acid complex instead of Mn sulfate. Dietary treatment began at estrus synchronization (approximately 20 d before estrus) and continued through 12 dpe when gilts were euthanized and tissues were collected. Protein and total RNA extracts from the CL were used for proteomic analysis via label-free liquid chromatography with tandem mass spectrometry to assess global protein abundance and quantitative real-time polymerase chain reaction (qRT-PCR ) to assess specific mRNA abundance, respectively. Compared with CON, 188, 382, and 401 proteins were differentially abundant ( P < 0.10) in TRT1, TRT2, and TRT3, respectively. Gene Ontology enrichment software revealed that proteins involved in P4 signaling and cholesterol synthesis were downregulated in CL of gilts fed Mn–amino acid complex compared with controls. Quantitative RT-PCR showed that relative transcript abundance of genes encoding steroidogenic enzymes ( CYP11A1 and StAR ) in CL tissue was decreased in gilts from TRT2 compared with CON ( P = 0.02), but TRT1 and TRT3 were not affected ( P ≥ 0.30). Collectively, these data support our hypothesis that a more bioavailable dietary Mn source may influence luteal function by altering the abundance of protein and mRNA involved in steroidogenesis.